Improvement of Cheilitis granulomatosa after Dental Treatment - Ryosuke Sasaki; Kayoko Suzuki; Teppei Hayashi; Hiroshi Inasaka; Kayoko Matsunaga (Karger Publishers, 2011)
A 38-year-old male suffered from swelling of the lower lip for 3 months. Neither facial nerve palsy nor fissuring of the tongue was present. Histological examination of a biopsy taken from the lower lip revealed non-caseous epithelioid cell granulomas, suggestive of cheilitis granulomatosa. Patch testing revealed positive reactions to mercury chloride and amalgam. His symptoms markedly improved 3 months after treatment of the apical periodontitis and replacement of dental crowns. As his dental crowns did not contain mercury, we believe that the cheilitis granulomatosa may have been related to the focal dental infection.